The role of formal vs. informal child protection systems in the context of conflict prevention and sustainable peacebuilding - Kodjasinska, Bojana (Филозофски факултет, Скопје, 2018)
The main research of this master thesis will focus on the formal and informal child protection systems and their contribution towards conflict prevention and sustainable peacebuilding. The objective of the thesis is to evaluate both systems and how they can impact the conflict prevention and the sustainable peacebuilding. By carefully analyzing a few previously selected case studies, the thesis will try to elaborate which one is in greater advantage of having the child protection system in question. The study is going to look at examples on how these states are coping with the issues in their area. It is given that children from all around the world have a right to human dignity, as well as to their physical and psychological integrity. The right to protection from all forms of violence is an inherent one and it means that no matter their nationality, place of birth, gender, age, national or ethnic origin, color, religion, language or any other status, each child has the very right to live a life without harm. Regardless of their given rights, children from all over the world face myriad risks such as: child abuse, separation from their parents or caregivers, sexual abuse, violence in their schools or communities, dangerous diseases like HIV and AIDS, early marriage, child pregnancy, justice-related issues, living and working on the streets, becoming child soldiers and many more. Child protection systems work closely and towards establishing and implementing many measures so that children can grow in safe and stable environments. After the final analysis, the thesis will try to prove which child protection system, whether the formal one that many governments have adopted or the informal child protection system, that operates with the help of NGOs and similar organizations, is better to have in order to have a sustainable peacebuilding.
Магистерска теза одбранета во 2018 година на Филозофскиот факултет во Скопје, под менторство на проф. д–р Маја Геровска Митев.
Keywords: child protection systems, formal child protection system, informal child protection system, children, peacebuilding, sustainable, conflict prevention, risks, actors, programs